Rational Antecedent Framework of Brand Satisfaction in the Industrial Market: Assessing Rational Perceived Quality and Rational Perceived Value Roles - Susanti, Vonny; Sumarwan, Ujang; Simanjuntak, Megawati; Yusuf, Eva Z (International Review of Management and Marketing, 2019)
Referring to the traditional paradigm, the industrial decision process is most likely influenced by rational aspects; is this perspective still relevant? The purpose of this paper is to explore further the role of rational satisfaction’s antecedents, particularly perceived quality and perceived value. This study conducts a literature review and an in-depth analysis of 10 papers published by reputable Scopus index publishers, with respondents from various industries and time horizon of the last five years. This study finds that rational aspects of perceived quality and perceived value influence satisfaction directly, moreover rational perceived quality influences perceived value, and indirectly influences brand satisfaction. However, the study finds that the emotional aspects are involved; although the final decision process is a dual process, the rational aspects still dominate the process of taking final decision. Keywords: perceived quality, perceived value, customer satisfaction, rational evaluation, brand equity JEL Classifications: M31, L10 DOI: https://doi.org/10.32479/irmm.9017